Official letter book of Gov. William Tryon of North Carolina, 1764-1771 - Tryon, William, 1729-1788
William Tryon's official letter book containing copies of letters and documents relating to his work as colonial governor of North Carolina; with references concerning drawing a boundary between North Carolina and South Carolina; talks with the Cherokee Indians; the establishment of a postal service; working with the Propagation of the Gospels in Foreign Parts; establishing the Church of England in North Carolina; strengthening the defenses of the colony; maintaining better communication with Great Britain; and other events. A notation prefixed indicated that this collection contained letters not preserved in the State Papers Office in London.